Diagnostic and prognostic impact of copeptin and high-sensitivity cardiac troponin T in patients with pre-existing coronary artery disease and suspected acute myocardial infarction. Issue 7 (15th February 2012) - Potocki, Mihael; Reichlin, Tobias; Thalmann, Simone; Zellweger, Christa; Twerenbold, Raphael; Reiter, Miriam; Steuer, Stephan; Bassetti, Stefano; Drexler, Beatrice; Stelzig, Claudia; Freese, Michael; Winkler, Katrin; et al.
Abstract : Objective: The early diagnosis of acute myocardial infarction (AMI) can be particularly challenging in patients with known coronary artery disease (CAD) due to pre-existing ECG changes and chronic increases in cardiac troponin (cTn) levels. Design: Of 1170 consecutive patients presenting with symptoms suggestive of AMI, 433 (37%) with pre-existing CAD were analysed in a prospective multicentre study and the diagnostic and prognostic impact of copeptin in combination with either fourth generation cardiac troponin T (cTnT) or high-sensitivity cTnT (hs-cTnT) was evaluated. Results: AMI was the final diagnosis in 78 patients with pre-existing CAD (18%). Copeptin was significantly higher in patients with AMI than in those without (26 pmol/l (IQR 9–71) vs 7 pmol/l (IQR 4–16), p<0.001). The diagnostic accuracy for AMI as quantified by the area under the receiver operating characteristic curve (AUC) was significantly higher for the combination of copeptin and cTnT than for cTnT alone (0.94 vs 0.86, p<0.001). The combination of copeptin and hs-cTnT (0.94) was trending to superiority compared with hs-cTnT alone (0.92, p=0.11). The combination of copeptin and the cTn assays was able to improve the negative predictive value up to 99.5% to rule out AMI. Copeptin was a strong and independent predictor of 1-year mortality (HR 4.18–4.63). Irrespective of cTn levels, patients with low levels of copeptin had an excellent prognosis compared with patients with raised levels of both copeptin and cTn (360-day mortality 2.8–3.6% vs 23.1–33.8%, p<0.001). Conclusion: In patients with pre-existing CAD, copeptin significantly improves the diagnostic accuracy if used in addition to cTnT, but only trended to superiority compared with hs-cTnT alone. Copeptin provides independent prognostic information, largely by overcoming the challenging interpretation of mild increases in hs-cTnT. Clinical trial registration number: ClinicalTrials Gov number NCT00470587 .